2020
DOI: 10.1016/j.hrthm.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of catheter ablation on arrhythmia burden in low-risk patients with paroxysmal atrial fibrillation: The CLOSE to CURE study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 39 publications
3
68
1
Order By: Relevance
“…The use of force‐sensing catheters, which allows better control during catheter manipulation, seemed to improve the clinical outcome; however, acute and late PV gap reconnections still occurred, and outcome data from related studies appeared inconsistent 16–18 . In the absence of real‐time RF lesion assessment, the AI, integrating contact force, power, and ablation duration in a weighted formula, has been validated to predict lesion formation and to further improve clinical outcome after the AF ablation 11,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of force‐sensing catheters, which allows better control during catheter manipulation, seemed to improve the clinical outcome; however, acute and late PV gap reconnections still occurred, and outcome data from related studies appeared inconsistent 16–18 . In the absence of real‐time RF lesion assessment, the AI, integrating contact force, power, and ablation duration in a weighted formula, has been validated to predict lesion formation and to further improve clinical outcome after the AF ablation 11,12 …”
Section: Discussionmentioning
confidence: 99%
“…The use of force‐sensing catheter enables visual contact/proximity information between the catheter and the myocardium to optimize the catheter manipulation during the point‐by‐point radiofrequency (RF) ablation. Moreover, the ablation index (AI), incorporating contact force, power, and ablation duration in a weighted formula, has been validated to predict lesion formation and to improve clinical outcome after AF ablation 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Such an indicator would be a lowerbound or underestimate of the eventual 12-month success rate, for example in the recent CLOSE to CURE study, freedom from recurrent arrhythmia was 69% during the 3-month blanking period versus 87% at 12 months, both measured by continuous loop monitoring. 30…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, continuous monitoring with ICMs has emerged as the gold standard for AF detection with significantly higher rates of arrhythmia detection over longer periods of monitoring. Three recent studies have evaluated the role of ICM for rhythm monitoring following AF ablation: Continuous Monitoring after AF Ablation: the LINQ AF study; Cryoballoon or Radiofrequency Ablation for AF Assessed by Continuous Monitoring (CIRCA DOSE); and the CLOSE‐Guided PV Isolation as Cure for Paroxysmal AF (CLOSE to CURE) 22–24 . In addition to good arrhythmia‐free survival, these studies demonstrated even greater reductions in AF burden, which may be a more meaningful measure of the benefit of ablation.…”
Section: Discussionmentioning
confidence: 99%